Perl best practices - Conway, Damian, 1964- (O'Reilly, 2005)
Many programmers code by instinct, relying on convenient habits or a "style" they picked up early on. They aren't conscious of all the choices they make, like how they format their source, the names they use for variables, or the kinds of loops they use. They're focused entirely on problems they're solving, solutions they're creating, and algorithms they're implementing. So they write code in the way that seems natural, that happens intuitively, and that feels good. But if you're serious about your profession, intuition isn't enough. Perl Best Practices author Damian Conway explains that rules.